Changes in chewing and swallowing secondary to allergic rhinitis and asthma in children and adolescents - integrative review - Silva, Michele Rocha da; Cardoso, Maria Cristina de Almeida Freitas (Distúrbios da Comunicação, 2019)
Introduction: Asthma and allergic rhinitis have been considered as manifestations of the same syndrome, since they have common epidemiological, genetic and pathophysiological bases. The interaction between difficulty in breathing function, asthma and allergic rhinitis may promote changes in the stomatognathic system, such as chewing and swallowing functions, as well as anatomical and functional changes in facial and somatic growth. Objective: To perform an integrative review of chewing and swallowing assessment in children and teenagers with rhinitis and asthma. Materials and Methods: We searched the Lilacs, MedLine, PubMed and Scielo databases for articles on swallowing and chewing in children and teenagers with asthma and rhinitis in January and February 2017, and this research was updated in June 2018. Results: A total of 2,537 articles were found, but only five presented the eligibility criteria. Discussion: Few studies regarding the topic were found. Of the five articles selected, three inferred to find no alterations and two found altered patterns, relating to the nasal obstruction factor. More research is needed on the subject. Conclusion: There is no scientific evidence to support the presence of chewing and swallowing disorders due to asthma and rhinitis in children and teenagers.